"Brown girls can't be gay": Racism experienced by queer South Asian women in the Toronto LGBTQ community. Issue 3 (3rd July 2019) - Patel, Sonali
Abstract: The absence of scholarship on South Asian discrimination in Western queer discourse contributes to a narrative that South Asians are not subjected to racially charged forms of discrimination in the LGBTQ community, which is fundamentally untrue. This article presents narrative-based accounts of nine queer South Asian women in Toronto, Canada, to examine the ways in which they experience racial discrimination in the LGBTQ community, and the impact that this mistreatment has on identity formation and connectivity to queer spheres. It finds that queer South Asian women experience racial discrimination in the form of racially charged microaggressions, which are evidenced through expectations of assimilation to Western-normative performances of queer identity and erasure of South Asian culture in the LGBTQ community. Further, it reveals that Toronto's LGBTQ community perpetuates a culture of White privilege that discredits the intersectional identity of queer South Asian women, and consequently invisibilizes, alienates, and revokes agency from these women who do not fit the majority's conceptualizations about what a queer woman looks like.